(untitled) (Progressive Agriculture, 2019)
The present experiment was conducted at the research field of Patuakhali Science and Technology University (PSTU), Patuakhali to evaluate the Performance of hybrid boro rice (genotypes) in coastal area of Bangladesh. The experiment consisted of five rice varieties as treatment such as Arize Tej, Tea Sakti, Shathi and BRRI Dhan 28. Data were collected on morphological characters such as plant height, number of leaves plant-1 and leaf area hill-1, growth characters such as leaf area index (LAI), crop growth rate (CGR) and relative growth rate (RGR), yield and yield components such as number of effective tillers hill-1,number of non effective tillers hill-1, panicle length, number of filled grains panicle-1, number of unfilled grains panicle-1, 1000 grain weight, grain yield, straw yield, biological yield and harvest index (%) were recorded. The experiment was laid out in a completely randomized block design (RCBD) with three replications. The collected data were analyzed statistically and means were adjudged by DMRT at 5% level of probability. Among the five varieties the Arize Tej gave the highest performance. From the above investigated results, it was observed that the Arize Tej was the most efficient for better growth and higher yield of hybrid boro rice genotypes grown in coastal area of Bangladesh. Progressive Agriculture 30 (2): 186-193, 2019